Web-Based Employee Recruitment Information System Using Mamdani Fuzzy Logic - Nurul Afifah; Asep Muhidin; Sophian Andhika Sardi (Ali Institute or Research and Publication, 2026)
This study introduces a novel integration of the Mamdani Fuzzy Inference System (FIS) with a web-based recruitment platform for Special Job Fair (BKK) institutions at vocational schools a context not previously addressed in the fuzzy decision-support literature. The current manual process at BKK Jaya Abadi SMKN 1 Bukateja relies on paper-based workflows, causing data loss risks, prolonged processing times, and subjective multi-criteria evaluation. The proposed system uses three input variables psychotest, interview, and health scores processed through fuzzification, an 18-rule inference base, MAX aggregation, and centroid defuzzification to generate objective recruitment recommendations. Testing on 35 applicant records yielded MAPE = 4.29% and accuracy = 95.71%, outperforming both the manual assessment baseline (MAPE = 12.86%, accuracy = 87.14%) and a simple weighted sum alternative (MAPE = 8.42%, accuracy = 91.58%). A paired t-test (α = 0.05) confirmed that accuracy differences are statistically significant. According to Lewis (1982), the system falls in the